Where is the Field? The Experience of Migration Viewed through the Prism of Ethnographic Fieldwork - Hirvi, Laura; Snellman, Hanna (Finnish Literature Society / SKS, 2012)
The book sheds light on the experiences of immigrants in different parts of the world and other insightful reflections on the art of carrying out fieldwork in the present day, when the task of locating the 'field' seems to present a particular challenge for researchers. This book is of interest to experienced ethnographers working in the discipline of migration studies and also to scholars conducting ethnographic research in other fields.